Teaching assistive technology in undergraduate courses in occupational therapy in the State of São Paulo - Teodoro, Marina Alves [UNESP]; Rodrigues, Ana Cláudia Tavares [UNESP]; Baleotti, Luciana Ramos [UNESP] (FapUNIFESP (SciELO), 2023)
Introduction: Knowledge about assistive technology is related to aspects of the field of occupational therapy, thus, it is questioned whether such knowledge has been addressed in undergraduate courses. Objectives: To identify the undergraduate courses in occupational therapy in the state of São Paulo that offer disciplines related to assistive technology, identify the disciplines, their respective workloads and the content present in each of them. Method: The sample consisted of eight universities, five public and three private. The search was made in the curricular matrices, teaching plans of specific and non-specific disciplines, objectives and contents available online or requested from the course coordinator. Descriptive data analysis was performed. Results: It was found that assistive technology content was offered in the investigated universities, with a difference between the workload and the content offered. The analysis by assistive technology application area showed that the content on orthoses is offered in 100% of the analyzed courses, followed by assistive products for the performance of daily activities and prostheses, both contents found in 75% of the courses; mobility equipment; accessibility and universal design in 62.5%; alternative communication in 50% of the courses. Conclusion: The results point to the relevance of greater homogeneity of content between the investigated universities and suggest that this study has the potential to foster discussions about the formation of occupational therapists in the assistive technology area, since the results come from the analysis of undergraduate courses located in the state which has the largest number of occupational therapy courses in Brazil.
Ensino de tecnologia assistiva nos cursos de graduação em terapia ocupacional do Estado de São Paulo
Keywords: Assistive Technology; Higher Education; Occupational Therapy; Professional Qualification